Effect of References And Services on Customer Decisions in Selecting Rahn Products - Septa Dwi Ayuningtyas; Mashuri Toha (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam (e-Journal), 2022)
Many people have lost their livelihoods due to the COVID-19 pandemic. BMT carries out fundraising activities by the community, distributes funds to the community and provides services in its functions as a non-bank financial institution. KSPPS BMT NU is one of the sharia-based financing solutions in Sumenep and is expected to minimize loan shark practices or even eliminate moneylender practices in villages in the Sumenep district. The method used is quantitative. Explanatory research type. Data collection techniques using questionnaires and documentation. A population of 1,081 was taken in the last six months, from July to December 2021. The sampling technique used non-probability sampling was 92 respondents. Furthermore, the validity and reliability tests were carried out with SPSS version 21. The results showed that the reference effect did not have a positive and significant impact but partially influenced customer decisions in choosing rahn products. This means that reference groups cannot always control a consumer, but it depends on whether the consumer wants to select the product or not with various considerations. Meanwhile, service has a positive and significant effect on customer decisions in choosing rahn products. That way, the higher the quality of service a company performs, the higher the customer's decision to select rahn products at KSPPS BMT NU Pragaan branch.